Unraveling the effects of tropical cyclones on economic sectors worldwide: direct and indirect impacts - Kunze, Sven (Discussion paper series, 2020)
This paper unravels the contemporaneous, lagged, and indirect effects of tropical cyclones on annual sectoral growth worldwide. The main explanatory variable is an area weighted measure for local tropical cyclone intensity based on meteorological data, which is included in a panel analysis for a maximum of 213 countries over the 1971-2015 period. I find a significantly negative influence of tropical cyclones on three sector aggregates including agriculture, infrastructure, as well as trade and tourism. In subsequent years, tropical cyclones negatively affect nearly all sectors. However, the Input-Output analysis shows that production processes are sticky and indirect economic costs are low.
Keywords: Graue Literatur